Is life satisfaction associated with future mental health service use? An observational population-based cohort study. Issue 4 (29th April 2022) - Michalski, Camilla A; Diemert, Lori M; Hurst, Mack; Goel, Vivek; Rosella, Laura C
Abstract : Objective: To investigate the prospective association between life satisfaction and future mental health service use in: (1) hospital/emergency department, and (2) outpatient settings. Design and setting: Population-based cohort study of adults from Ontario, Canada. Baseline data were captured through pooled cycles of the Canadian Community Health Survey (CCHS 2005–2014) and linked to health administrative data for up to 5 years of follow-up. Participants: 131 809 Ontarians aged 18 years and older. Main outcome measure: The number of mental health-related visits in (1) hospitals/emergency department and (2) outpatient settings within 5 years of follow-up. Results: Poisson regression models were used to estimate rate ratios in each setting, adjusting for sociodemographic measures, history of mental health-related visits, and health behaviours. In the hospital/emergency setting, compared to those most satisfied with life, those with the poorest satisfaction exhibited a rate ratio of 3.71 (95% CI 2.14 to 6.45) for future visits. In the outpatient setting, this same comparison group exhibited a rate ratio of 1.83 (95% CI 1.42 to 2.37). When the joint effects of household income were considered, compared with the highest income and most satisfied individuals, the least satisfied and lowest income individuals exhibited the highest rate ratio in the hospital/emergency setting at 11.25 (95% CI 5.32 to 23.80) whereas in the outpatient setting, the least satisfied and highest income individuals exhibited the highest rate ratio at 3.33 (95% CI 1.65 to 6.70). Conclusion: The findings suggest that life satisfaction is a risk factor for future mental health visits. This study contributes to an evidence base connecting positive well-being with health system outcomes.